1963
DOI: 10.1111/j.1365-2672.1963.tb01150.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Sulphate Reduction and the Development of Alkalinity. III. Experiments under Natural Conditions in the Wadi Natrûn

Abstract: Evidence that microbial sulphate reduction is mainly responsible for the formation of the natron (hydrated Na2CO3) deposits in Wadi Natrûn is presented. The sulphate in the infiltrating water is reduced during passage through the surrounding waterlogged soil and the bicarbonate formed is later concentrated by evaporation in the lakes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1977
1977
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(15 citation statements)
references
References 4 publications
0
15
0
Order By: Relevance
“…The occurrence of sulfate-reducing bacteria has been reported from nonsaline environments as well as from those with all degrees of salinity up to saturation (Abd-el-Malek and Rizk, 1963;Skyring, Jones, and Goodchild, 1977;Triiper, 1969;ZoBell, 1957). Of the validly described species, only Desulfovibrio salexigens and Desulfovibrio desulfuricans var.…”
Section: Habitatsmentioning
confidence: 95%
“…The occurrence of sulfate-reducing bacteria has been reported from nonsaline environments as well as from those with all degrees of salinity up to saturation (Abd-el-Malek and Rizk, 1963;Skyring, Jones, and Goodchild, 1977;Triiper, 1969;ZoBell, 1957). Of the validly described species, only Desulfovibrio salexigens and Desulfovibrio desulfuricans var.…”
Section: Habitatsmentioning
confidence: 95%
“…were also observed. Abd E1 Malek and Rizk (1963) concluded that the high concentrations of sulphate and organic matter in the sediments and the mud surrounding the lakes favour the development of sulphate-reducing bacteria and lead to the evolution of considerable amounts of hydrogen sulphide and carbon dioxide. Imhoff et al (1979) observed mass developments of sulphide-oxidizing phototrophic bacteria in the upper sediment layers and in the water of the lakes.…”
Section: Perennial Saline Lakesmentioning
confidence: 99%
“…Its average length is about 60 km and average width about 10 km. The bottom of the wadi is 23 m below sea-level and 38 m below the water-level of Rosetta branch of the Nile (Abd E1 Malek and Rizk, 1963). The lowest part of the depression, encircled by contour zero, covers an area of about 272 km 2.…”
Section: Study Areamentioning
confidence: 99%
“…Its average length is about 60 km and average width about 10 km. The bottom of the wadi is 23 m below sealevel and 38 m below the water-level of the Rosetta branch of the Nile (Abd E1 Malek and Rizk, 1963). The lowest part of the depression, encircled by contour zero, covers an area of about 272 km 2.…”
Section: Introductionmentioning
confidence: 99%